"Can't You Just Cure It by Not Eating Sugar?!": A Review of the Children with Diabetes Site, childrenwithdiabetes.com. Issue 4 (2nd October 2019) - Phillips, Kat
Abstract: Type 1 diabetes (T1D) diagnoses are steadily rising, so support for families, caregivers, and those diagnosed with T1D is equally on the rise. This specific need, while addressed by many reliable and popular organizations like the CDC and American Diabetes Association, do not focus on this specific population. The Children with Diabetes organization hosts www.childrenwithdiabetes.com, a trusted and reliable source of support and information. This community is comprised of both medical providers and those affected by T1D. This review will cover the main points of the site, addresses its strengths, and highlights some of the community outreach it supports.